Answer

Verified

412.2k+ views

**Hint:**In this problem, first we will multiply the given equations. Then, we will use the law of exponents which is given by ${a^m} \times {a^n} = {a^{m + n}}$. After simplification, we will get the value of $x$. Then, we will find the value of $y$. Then, we will get the required value.

**Complete step-by-step answer:**

In this problem, we have two equations. Let us write the given equations.

${2^{2x - y}} = 32 \cdots \cdots \left( 1 \right)$ and ${2^{x + y}} = 16 \cdots \cdots \left( 2 \right)$

Now we will multiply the equation $\left( 1 \right)$ and $\left( 2 \right)$. Therefore, we get

$

\left( {{2^{2x - y}}} \right) \times \left( {{2^{x + y}}} \right) = 32 \times 16 \\

\Rightarrow \left( {{2^{2x - y}}} \right) \times \left( {{2^{x + y}}} \right) = {2^5} \times {2^4} \cdots \cdots \left( 3 \right) \\

$

Now we will use the law of exponents which is given by ${a^m} \times {a^n} = {a^{m + n}}$ on both sides of equation $\left( 3 \right)$. Therefore, we get

$

{2^{2x - y + x + y}} = {2^{5 + 4}} \\

\Rightarrow {2^{3x}} = {2^9} \\

\Rightarrow 3x = 9\quad \left[ {\because {a^x} = {a^y} \Rightarrow x = y} \right] \\

\Rightarrow x = \dfrac{9}{3} \\

\Rightarrow x = 3 \\

$

Now we will substitute the value $x = 3$ in either equation $\left( 1 \right)$ or equation $\left( 2 \right)$ to find the value of $y$. Let us substitute the value $x = 3$ in equation $\left( 1 \right)$. Therefore, we get

$

{2^{2\left( 3 \right) - y}} = 32 \\

\Rightarrow {2^{6 - y}} = {2^5} \\

\Rightarrow 6 - y = 5\quad \left[ {\because {a^x} = {a^y} \Rightarrow x = y} \right] \\

\Rightarrow y = 6 - 5 \\

\Rightarrow y = 1 \\

$

Now we have $x = 3$ and $y = 1$. Therefore, ${x^2} + {y^2} = {\left( 3 \right)^2} + {\left( 1 \right)^2} = 9 + 1 = 10$.

Therefore, if ${2^{2x - y}} = 32$ and ${2^{x + y}} = 16$ then ${x^2} + {y^2}$ is equal to $10$.

**So, option B is the right answer**

**Note:**We can also solve this problem by using different methods. In one of the methods, we will use one property which is given by ${a^x} = {a^y} \Rightarrow x = y$. After using this property in both given equations, we will get two linear equations in $x$ and $y$. Then, we will use a simple elimination method to find the values of $x$ and $y$. Then, we will get the required value.

Recently Updated Pages

The base of a right prism is a pentagon whose sides class 10 maths CBSE

A die is thrown Find the probability that the number class 10 maths CBSE

A mans age is six times the age of his son In six years class 10 maths CBSE

A started a business with Rs 21000 and is joined afterwards class 10 maths CBSE

Aasifbhai bought a refrigerator at Rs 10000 After some class 10 maths CBSE

Give a brief history of the mathematician Pythagoras class 10 maths CBSE

Trending doubts

Difference Between Plant Cell and Animal Cell

Give 10 examples for herbs , shrubs , climbers , creepers

Name 10 Living and Non living things class 9 biology CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Change the following sentences into negative and interrogative class 10 english CBSE

Write a letter to the principal requesting him to grant class 10 english CBSE

Fill the blanks with proper collective nouns 1 A of class 10 english CBSE

Write the 6 fundamental rights of India and explain in detail